Gestión pedagógica en el aula: clima social escolar, desde la percepción de estudiantes y profesores del séptimo año de educación básica del centro educativo urbano “Rafael María García” y del centro educativo rural “Juana de Ibarborou” de la provincia del Cañar, 2011-2012. - Matute Gonzalez, Mayra Margarita (2013)
The problematización of the Pedagogic Management in the classroom of class believes a social school climate, from the perception of students and teachers, with the intention of knowing the pedagogic management and the social climate of classroom, as elements of measure and description of the environment in which there develops the educational process of the students of the seventh year of General Básica urban Education of the schools "Rafael Maria García", and of the rural center "Juan de Ibarborou". The investigated sample they were the children of the seventh year of EGB, where there was applied an exploratory descriptive investigation, using methods as analytical - synthetically, inductively, deductively, statistically to analyze the results and the hermeneutic one that facilitates the bibliographical interpretation, of equal way the instruments empelados were the questionnaire CES of Moos and Trickett Ecuadoran adjustment for teachers and for students, and the questionnaires of autoevaluation to the management of the learning, with his respective dimensions, and subscales. There is recommended the complete reading of this study due to the great importance that has the climate of classroom in the quality of education given by teachers.